Effect of processed spent bleaching earth as partial cement replacement on thermal conductivity and porosity of foamed concrete - Mohammad Asyraf, Mohd Faridi Yusli (2018)
Foamed concrete is categorized as a lightweight concrete containing air voids. The only difference is that foamed concrete does not contain coarse aggregate in its mixture. Foamed concrete is produced by inducing foam into the slurry of cement mixing with silica sand. In practice, the cement is usually replace with lime. Processed Spent Bleaching Earth (PSBE) is one of the latest Crude Palm Oil (CPO) product. After it has been degummed and bleached, it will come in fine particle and it is classified as a good pozzolanic material. The study investigates the suitability of PSBE as partial cement replacement. The scope of study includes the thermal conductivity and porosity percentage. 10%, 20% and 30% of PSBE will be replacing cement. Foaming agent is used to form air void in foamed concrete. The results turns out that for thermal for 10% PSBE cement replacement at 28 days gets the best reading which is 0.52 W/m.K. For porosity, the result shows that porosity for 30% PSBE foamed concrete achieved the result at 90 days with 17.9% compared to controlled sample. 21.4%. Foamed concrete density also increase when the PSBE percentage increase. Generally thermal conductivity and porosity percentage is one of pozzolanic material characteristic and this study will emphasize this two aspect.